2016
DOI: 10.3389/fmicb.2016.00326
|View full text |Cite
|
Sign up to set email alerts
|

Propagation and Characterization of Influenza Virus Stocks That Lack High Levels of Defective Viral Genomes and Hemagglutinin Mutations

Abstract: Influenza virus infections are responsible for more than 250,000 deaths annually. Influenza virus isolation, propagation, and characterization protocols are critical for completing reproducible basic research studies and for generating vaccine seed stocks. Detailed protocols for the isolation and identification of influenza virus have been recently reported (Eisfeld et al., 2014). However, there are few standardized protocols focused on the propagation and characterization of viral isolates, and as a result, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 48 publications
1
72
0
Order By: Relevance
“…The first was a standard stock grown from low dose in embryonated chicken eggs; the second was produced in eggs following triple plaque purification to limit the abundance of DI particles (12, 28); and the third was generated by serial passage in cell culture under high multiplicity conditions, which leads to enrichment of DI particles (6, 12, 28). An example of the raw data obtained by ddPCR is shown in Figure 2, with panel A displaying results acquired with terminal PB2 primers and panel B showing results obtained with internal PB2 primers, both combined with cDNA templates derived from the Pan/99wtHis-MDCK P3 virus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first was a standard stock grown from low dose in embryonated chicken eggs; the second was produced in eggs following triple plaque purification to limit the abundance of DI particles (12, 28); and the third was generated by serial passage in cell culture under high multiplicity conditions, which leads to enrichment of DI particles (6, 12, 28). An example of the raw data obtained by ddPCR is shown in Figure 2, with panel A displaying results acquired with terminal PB2 primers and panel B showing results obtained with internal PB2 primers, both combined with cDNA templates derived from the Pan/99wtHis-MDCK P3 virus.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, the impact of DI particles on experimental outcomes and natural IAV infections may be substantial. Xue et al recently reported a rigorous method for preparation of influenza A virus stocks designed to limit the prevalence of DI particles (28). Despite this important advance, a robust assay for the quantification of DI segments is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…However, the burden of defective viral particles can be reduced by growing virus for a 214 short amount of time and at a low MOI, as defective viral particles increase in frequency 215 when viruses are grown at a high MOI where complementation of deleterious genotypes 216 7/53 can occur [79]. The even read coverage across the polymerase segments in our data 217 ( Fig.…”
mentioning
confidence: 81%
“…DVGs are present in live attenuated vaccines against polio, measles and influenza viruses 76,[123][124][125][126] . However, their impact in the development of protective immunity and vaccine efficacy has not been formally assessed.…”
Section: Use As Antivirals and Vaccine Adjuvantsmentioning
confidence: 99%